1994
DOI: 10.1021/bi00169a025
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Expression, and Properties of a Recombinant Chimeric Human Protein C with Replacement of Its Growth Factor-like Domains by Those of Human Coagulation Factor IX

Abstract: The cDNA encoding a chimeric human protein C (PC), in which its epidermal growth factor-(EGF) like regions have been replaced with equivalent structures from human factor IX (fIX), was constructed and the gene product was expressed in human 293 cells. A molecular subpopulation of the recombinant chimeric protein (r-[PC/delta EGF-1,2/delta fIXEGF-1,2]) was purified that contained the full complement (9 residues/mol) of gamma-carboxyglutamic acid (Gla). After conversion by thrombin to its activated form (r-[APC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Two mAbs, viz., C3, which was known to possess a Ca 2 *-independent epitope in the EGF1 domain of PC (Heeb ef a/., 1988;Yu et a/., 1994), and RIT, which was found in this study to also react with sites within this same module, were found to be refractive to the variant r-[R 91 A/E 92 A]PC. Not only did this investigation enable us to characterize further the integrity of the mutants, but it also allowed a more precise definition of the epitopes of this important group of mAbs.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Two mAbs, viz., C3, which was known to possess a Ca 2 *-independent epitope in the EGF1 domain of PC (Heeb ef a/., 1988;Yu et a/., 1994), and RIT, which was found in this study to also react with sites within this same module, were found to be refractive to the variant r-[R 91 A/E 92 A]PC. Not only did this investigation enable us to characterize further the integrity of the mutants, but it also allowed a more precise definition of the epitopes of this important group of mAbs.…”
Section: Discussionsupporting
confidence: 50%
“…The intrinsic fluorescence of PC and similar proteins of this class is known to undergo large alterations upon binding of Ca 2+ , which are due in part to conformational rearrangements of the Gla domains of these proteins. Since it has been demonstrated previously that this mAb was reactive against the EGF1 domain of PC (Yu et a/., 1994), we are now able to further define this epitope from the above data as primarily residing at the COOH-terminus of this domain with at least some involved amino acid residues located in the last disulfide loop and extending into the polypeptide linker between EGF1 and EGF2. Examples of the titration data are illustrated in Figure 2 for wt r-PC and r-[D 71 A]PC.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…fVII, IX, X, and XII) (50,51) and anticoagulant proteins (e.g. thrombomodulin and protein C) (52,53). As shown in Figs.…”
Section: Discussionmentioning
confidence: 96%
“…This mutant was activated by thrombomodulin-thrombin complex at ϳ70% of the rate obtained with the wild type protein C (52). The activated protein C mutant was also defective in inactivating FVa and FVIII/ FVIIIa in a PL-containing system (52). The decreased activity of activated protein C mutant was attributed to direct proteinprotein interaction and/or to misalignment of domains/recognition sites with its physiological substrates.…”
Section: Discussionmentioning
confidence: 98%